Answer:
y= -3 -6x/5
Step-by-step explanation:
6x+5y=-15
-6x -6x
-----------------------------------
5y = -15 - 6x
divide both sides by 5
5y/5= -15/5 - 6x/5
y= -3 -6x/5
Assuming the variables are constants, you isolate m. So move am to the left. K-am=emx. Now divide ex. This gives you, m=(K-am/ex)
Answer:
Here you go :)
Step-by-step explanation:
(2 1/3)(3 3/4)
= 7/3(3 3/4)
= 7/3(15/4)
= 35/4
= 8 3/4
I hope this helps, if it doesn't then just message me and ill be more than happy to help :)
Answer:
Hii i just know the 4 and 5 one
Step-by-step explanation:
4 one is exterior
5 one is included angle
Answer:
Step-by-step explanation:
y = -2
4x - 3y = 18
4x - 3(-2) = 18
4x + 6 = 18
4x = 12
x = 3
(3, -2)